All Solution‐Processed, Hybrid Light Emitting Field‐Effect Transistors. (5th June 2014) - Muhieddine, Khalid; Ullah, Mujeeb; Pal, Bhola N.; Burn, Paul; Namdas, Ebinazar B.
<x xml:space="preserve">Abstract</x> All solution‐processed, high performance hybrid light emitting transistors (HLETs) are realized. Using a novel combination of device architecture and materials a bilayer device comprised of an inorganic and organic semiconducting layer is fabricated and the optoelectronic properties are presented. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>